Should Ageism Be a Stratification Factor in Patients with Pancreatic Cancer? - El-Jurdi, Najla H; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
With ageism being a trend worldwide, and age being a known risk factor for pancreatic cancer, the optimal management of pancreatic cancer patients with advance age is becoming more and more of a pertinent discussion amongst GI oncologists, surgical oncologists and radiation oncologists that is being increasingly addressed in studies nowadays. In an attempt to answer the question of whether age should be a cultural bias in decision making in pancreatic cancer patients, we will review Abstracts #287, #310 and #332 that were presented in the 2014 ASCO Gastrointestinal Cancers Symposium. These abstracts explore whether neoadjuvant therapy should be offered to patients older than 75 years to increase the chances of bridging to surgical resectability (Abstract #287), if patients older than age 70 years would benefit from chemotherapy similar to younger patients (Abstract #310), also whether adjuvant radiation therapy and number of lymph nodes resected in patients older than 70 years correlates with overall survival (Abstract #332). Image: Tufts University. Boston, MA, USA